Performance assessment of a new optimization system for robotic SBRT MLC-based plans. (March 2020) - Calusi, Silvia; Doro, Raffaela; Di Cataldo, Vanessa; Cipressi, Samantha; Francolini, Giulio; Bonucci, Ivano; Livi, Lorenzo; Masi, Laura
Highlights: A critical analysis of plan quality evaluation was performed. Optimization with VOLO system highly reduce time required for plan optimization. Quality of VOLO-optimized plans is equivalent or higher than that of Sequential-optimized plans. Reliable plan quality comparison combining strong mathematical score and clinical evaluation. Abstract: Purpose: To assess the performance of a new optimization system, VOLO, for CyberKnife MLC-based SBRT plans in comparison with the existing Sequential optimizer. Methods: MLC-plans were created for 25 SBRT cases (liver, prostate, pancreas and spine) using both VOLO and Sequential. Monitor units (MU), delivery time (DT), PTV coverage, conformity (nCI), dose gradient (R50%) and OAR doses were used for comparison and combined to obtain a mathematical score (MS) of plan quality for each solution. MS strength was validated by changing parameter weights and by a blinded clinical plan evaluation. The optimization times (OT) and the average segment areas (SA) were also compared. Results: VOLO solutions offered significantly lower mean DT (−19%) and MU (−13%). OT were below 15 min for VOLO, whereas for Sequential, values spanned from 8 to 160 min. SAs were significantly larger for VOLO: on average 10 cm 2 versus 7 cm 2 . VOLO optimized plans achieved a higher MS than Sequential for all tested parameter combinations. PTV coverage and OAR sparing were comparable for both groups of solutions. Although slight differences in R50% and nCI were found, the parameters most affecting MS were MU and DT. VOLO solutions were selected in 80% of cases by both physicians with 88% inter-observer agreement. Conclusions: The good performance of the VOLO optimization system, together with the large reduction in OT, make it a useful tool to improve the efficiency of CK SBRT planning and delivery. The proposed methodology for comparing different planning solutions can be applied in other contexts.